Gaze Interaction and Applications of Eye Tracking
DOI: 10.4018/978-1-61350-098-9.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Gaze Interaction

Abstract: Gaze interaction, as understood in this book, provides a means to exploit information from eye gaze behaviour during human-technology interaction. Gaze can either be used as an explicit control method that enables the user to point at and select items, or information from the user’s natural gaze behaviour can be exploited subtly in the background as an additional input channel without interfering with normal viewing. This chapter provides a brief introduction to the potential for applied gaze tracking, with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Moreover, these children might take a longer time to operate/navigate computers compared with using gestures or vocalizations, particularly when they are novice users. Insufficient eye control skills at early stages of learning and cognitive demands might cause the children to tire easily which could decrease the efficiency of EGAT use over time [ 48 ]. Recent research showed children with complex needs normally used EGAT for up to two hours per day [ 17 ], which means they might use other modes of communication in communicative interactions in daily contexts more often.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these children might take a longer time to operate/navigate computers compared with using gestures or vocalizations, particularly when they are novice users. Insufficient eye control skills at early stages of learning and cognitive demands might cause the children to tire easily which could decrease the efficiency of EGAT use over time [ 48 ]. Recent research showed children with complex needs normally used EGAT for up to two hours per day [ 17 ], which means they might use other modes of communication in communicative interactions in daily contexts more often.…”
Section: Discussionmentioning
confidence: 99%
“…Since the participants were not restricted in their movement, we decided to also study their posture and its relation to fatigue, based on known relations of increased postural variations during low arousal periods in tasks [ 30 ], and observations of participants lowering themselves in the chair as the experiment progressed. Finally, we also studied performance measures commonly measured using eye-typing—typing speed, error rate, attended but not selected rate (ANSR) for keys and read text events ratio (RTE) [ 31 ]. ANSR and RTE are associated with the error rate during typing and accuracy of the gaze-typing system [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Users are able to interact with objects on a computer screen simply by moving their eyes rather than using a mouse or keyboard. This is made possible by a camera mounted on the screen that reads, within a few millimeters, where on the screen the person is gazing [1,2].…”
Section: Introductionmentioning
confidence: 99%